Four new records of arbuscular mycorrhizal fungi (Glomeromycota) associated with Agave karwinskii and A. angustifolia (Agavaceae) in Oaxaca, Mexico - Chimal Sánchez, Eduardo; Reyes Jaramillo, Irma; Salmerón Castro, Jose Yabin; Vázquez Pérez, Nancy; Varela Fregoso, Lucía (Instituto de Ecología, A.C., 2018)
Background and Aims: The agaves are a natural resource appreciated by about people from Oaxaca as food source and for the mescal production; however, there is scarce information the arbuscular mycorrhizal fungi (AMF) associated to them. The objective of this study is to contribute to the taxonomic knowledge of the AMF in Mexico with four new records; in particular, in mescal agaves of the semi-arid region of Oaxaca.Methods: In nine sites of the Central Valleys and the Southern Highlands of Oaxaca, rhizosphere soil was collected from three plants of Agave karwinskii and A. angustifolia to isolate the spores of AMF, and to make permanent preparations with polyvinyl lacto glicerol (PVLG) and reagent of Melzer. Morphological characters of the spores were used for taxonomic identification. The soil texture, the active pH (1:2.5 soil-water), the percentage of organic matter, the available phosphorus and the extractable bases Ca++, Mg++, K+ and Na+ were determined.Key results: Four species of Glomeromycota are cited for the first time from Mexico: Acaulospora minuta, A. papillosa, A. reducta and, Paraglomus bolivianum, all associated with the rhizosphere of Agave karwinskii and, the last two species, also with that of A. angustifolia. The AMF were registered in soils of thick texture, rich in calcium and poor in available phosphorus. The taxonomic descriptions and illustrations of the four species are presented.Conclusions: With these four new records, Acaulospora minuta, A. papillosa, A. reducta and P. bolivianum, 148 species of AMF are known from Mexico. Oaxaca is a state of high floristic diversity and a center of diversification of plants, among them agaves; however, the AMF have been barely studied and their taxonomic diversity is probably important.